Impact of Corporate Social Responsibility on Customer Satisfaction in Retail Enterprises in the Baltic Countries - Iveta LININA; Velga VEVERE (Communications of International Proceedings, 2020)
Domestic consumption is one of the cornerstones of any national economy. Particularly in the retail trade, the corporate social responsibility is a guarantee for the company's sustainable development and its competitiveness. To identify the impact factors of the corporate social responsibility, the authors have set out to investigate the customer satisfaction from three aspects - customer service quality, marketing activities, as well as product placement and shopping convenience. The authors examine the theoretical background of customer relationship formation and corporate social responsibility. Then they describe retail trade development tendencies in the Baltic countries and, by conducting a customer survey (1446 respondents) determine the main factors underlying the socially responsible relations with customers. This study gives retailers an understanding of the need for a socially responsible relationship with customers and points to specific aspects of this process in retailing that ensure the customer loyalty. The authors conclude that by understanding the main principles of customer relationship formation, the retail enterprise can manage these processes in the socially responsible way and that responsibility can be one of the tools for enhancing business competitiveness.
Keywords: Customer Satisfaction; Corporate Social Responsibility; Retailing; Customer Loyalty.